Strategi gereja-gereja daerah menyikapi tantangan pelayanan - Kaventius Pambayun (Sekolah Tinggi Teologi SAPPI Ciranjang, 2021)
The main task of the church is to proclaim the gospel of Christ and to shepherd His disciples (Matt. 28:19). In carrying out these two main tasks, God's church is faced with challenges that must be faced, because that is the reality of God's church ministry in this world (Matt. 10:6). This is also what churches in remote areas, especially Indonesia, are facing. Therefore, the church needs to think of a strategy that is strong, effective and targeted (contextual), but still based on Bible truth. Whatever the conditions, the church must remain missionary, because that is the reason for its existence in the midst of this world, namely to bring the Good News from the Lord Jesus Christ. This study uses a qualitative method with a narrative review approach. In this research, the strategies offered are: evangelism into the church, discipleship, training for evangelism, mentoring for evangelism practice, evangelism outside.